Coordination Conflicts between Urban Resilience and Urban Land Evolution in Chinese Hilly City of Mianyang - Qi Cao; Yudie Huang; Baisong Ran; Gang Zeng; Anton Van Rompaey; Manjiang Shi (Remote Sensing, 2021)
Urban resilience, the combinational characteristic of nature and society, that reflects the dynamic accumulation process that is multi-level and multi-dimensional. Particularly, the rational spatial distribution structure of land mixture and compactness is an effective way to improve urban resilience because the evolution of morphology and density of the urban land blocks in the process of land spatial conversion reflect the performance characteristics of complexity, diversity, stability, compactness, and connectivity. Therefore, we evaluated the relationship between urban resilience and land use and land cover (LULC) change, to find the keys to resilient urban development for urban land and space planning. In this study, taking the Chinese hilly city of Mianyang as an example, the results show: (1) the complexity of homogeneous patch shape and heterogeneous patch combination leads to the decrease of urban morphology resilience. (2) the development trend of LULC spatial layout and structure ratio were more rational with the increased of land mixing degree. (3) the speed and intensity of urban expansion were basically coordinated with the development of urban resilience. The research provides the new ideas, approaches, and toolkits for solving the intractable problems of urban spatial planning based on coordinating conflicts between urban resilience and urban land evolution.